2018
DOI: 10.12932/ap-131117-0196
|View full text |Cite
|
Sign up to set email alerts
|

Features and outcomes of immunoglobulin therapy in patients with Good syndrome at Thailand’s largest tertiary referral hospital

Abstract: Background: Good syndrome (GS) is an adult-onset immunodeficiency characterized by coexisting thymoma and hypogammaglobulinemia. Clinical course after treatment with intravenous immunoglobulin (IVIg) has rarely been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(24 reference statements)
1
0
0
Order By: Relevance
“…This does not necessarily translate into poor clinical outcome, as evidenced by the absence of worsening or new infection episodes in our patient after starting IVIG replacement. This is in parallel with a retrospective review which showed most patients (about 80%) had a significant reduction in the infection rates after IVIG treatment [ 9 , 10 ].…”
Section: Discussionsupporting
confidence: 62%
“…This does not necessarily translate into poor clinical outcome, as evidenced by the absence of worsening or new infection episodes in our patient after starting IVIG replacement. This is in parallel with a retrospective review which showed most patients (about 80%) had a significant reduction in the infection rates after IVIG treatment [ 9 , 10 ].…”
Section: Discussionsupporting
confidence: 62%